2007
DOI: 10.1038/sj.leu.2404834
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the p210BCR-ABL oncoprotein drives centrosomal hypertrophy and clonal evolution in human U937 cells

Abstract: Centrosomes play fundamental roles in mitotic spindle organization, chromosome segregation and maintenance of genetic stability. Recently, we have shown that centrosome aberrations occur early in chronic myeloid leukemia (CML) and are induced by imatinib in normal fibroblasts in vitro. To investigate the influence of BCR-ABL on centrosomes, we performed longterm in vitro experiments employing the conditionally p210BCR-ABL-expressing (tetracycline-inducible promoter) human monocytic cell line U937p210BCR-ABL/c6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 33 publications
(51 reference statements)
5
23
1
Order By: Relevance
“…Tight regulation of tyrosine kinase activity has also been proven crucial for maintaining centrosomal integrity: both constitutive BCR-ABL activation and abrogation of tyrosine kinase activity by specific inhibitors have been shown to lead to centrosomal aberrations. 25,[41][42][43] We do not regard our conclusionFdrawn from a functional point of viewFas contradictory to previous studies. These have hypothesized a functional role of centrosomal tyrosine kinase activity based on the centrosomal localization of fusion proteins and have particularly relied on the detection of centrosomal signal transduction.…”
Section: Centrosomes In Myeloproliferative Disorderscontrasting
confidence: 98%
“…Tight regulation of tyrosine kinase activity has also been proven crucial for maintaining centrosomal integrity: both constitutive BCR-ABL activation and abrogation of tyrosine kinase activity by specific inhibitors have been shown to lead to centrosomal aberrations. 25,[41][42][43] We do not regard our conclusionFdrawn from a functional point of viewFas contradictory to previous studies. These have hypothesized a functional role of centrosomal tyrosine kinase activity based on the centrosomal localization of fusion proteins and have particularly relied on the detection of centrosomal signal transduction.…”
Section: Centrosomes In Myeloproliferative Disorderscontrasting
confidence: 98%
“…[17] Recently, in a long-term in vitro study on a CML CP model we have established the functional link of p210BCR-ABL TK activity with centrosome amplification and clonal evolution. [23] This is in accordance with the observation that p210BCR-ABL and c-ABL are both centrosome associated proteins. [24] However, IM treatment did not prevent the development of centrosome amplification; but by itself induced centrosomal and/or cytogenetic alterations in several bcr-abl -negative cell line models and in vivo .…”
Section: Introductionsupporting
confidence: 87%
“…All cell lines were treated with therapeutic doses of IM (range: 1 to 10 μM) as performed in our previous studies. [23,26,27,42] In accordance with data from extensive studies on the dose-dependent effects and time kinetics of IM we applied lower IM doses (range: 1 μM to 2.5 μM) for leukemia-derived p210BCR-ABL-positive cells (KCL-22, BV-173, K562 and LAMA-84) than for p210BCR-ABL-negative cells (range: 2.5 μM to 10 μM). [4648] Treating CML cell lines with IM doses higher than 2.5 μM for a longer period than 48h impeded the collection of enough viable cells for Western blot analysis and Separase activity assays (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…As centrosome defects were indicated as en early detectable BCR-ABL Hits at Mitosis; Implications for Chromosomal Instability, Aneuploidy and Therapeutic Strategy 5 feature of CML, they have been proposed as a cause of karyotype instability and aneuploidy in CML progenitor cells as well as a valuable prognostic factor. In the long-term in vitro studies, using a cellular model of the chronic phase of CML, authors confirmed, that expression of BCR-ABL leads to significant centrosomal hypertrophy visible already after 4 weeks of BCR-ABL expression (Giehl et al, 2007). This increased upon the next 10 weeks of propagation and correlated with the clonal expantion of aneuploid cells.…”
Section: Centrosomal Multiplicationmentioning
confidence: 75%